Genome-based taxonomic rearrangement of Oceanobacter-related bacteria including the description of Thalassolituus hydrocarbonoclasticus sp. nov. and Thalassolituus pacificus sp. nov. and emended description of the genus Thalassolituus - Dong, Chunming; Wei, Lin; Wang, Jianning; Lai, Qiliang; Huang, Zhaobin; Shao, Zongze (Frontiers in Microbiology, 2022)
Oceanobacter-related bacteria (ORB) are a group of oligotrophic marine bacteria play an underappreciated role in carbon cycling. They have been frequently described as one of the dominant bacterial groups with a wide distribution in coastal and deep seawater of global oceans. To clarify their taxonomic affiliation in relation to alkane utilization, phylogenomic and comparative genomics analyses were performed based on currently available genomes from GenBank and four newly isolated strains, in addition to phenotypic and chemotaxonomic characteristics. Consistently, phylogenomic analysis robustly separated them into two groups, which are accordingly hydrocarbon-degrading (HD, Thalassolituus and Oleibacter) and non-HD (NHD, Oceanobacter). In addition, the two groups can also be readily distinguished by several polyphasic taxonomic characteristics. Furthermore, both AAI and POCP genomic indices within the HD group support the conclusion that the members of the genus Oleibacter should be transferred into the genus Thalassolituus. Moreover, HD and NHD bacteria differed significantly in terms of genome size, G + C content and genes involved in alkane utilization. All HD bacteria contain the key gene alkB encoding an alkane monooxygenase, which can be used as a marker gene to distinguish the members of closely related genera Oceanobacter and Thalassolituus. Pangenome analysis revealed that the larger accessory genome may endow Thalassolituus with the flexibility to cope with the dynamics of marine environments and thrive therein, although they possess smaller pan, core- and unique-genomes than Oceanobacter. Within the HD group, twelve species were clearly distinguished from each other by both dDDH and ANI genomic indices, including two novel species represented by the newly isolated strains alknpb1M-1T and 59MF3M-4T, for which the names Thalassolituus hydrocarbonoclasticus sp. nov. and Thalassolituus pacificus sp. nov. are proposed. Collectively, these findings build a phylogenetic framework for the ORB and contribute to understanding of their role in marine carbon cycling.